Taxonomic notes on Brandisia (Orobanchaceae) - Zhou, Zhuo; Chen, Zhe; Guo, Ze-Min; Do, Truong Van; Niu, Yang; Sun, Hang (Phytotaxa, 2024)
Field investigations and specimen examination revealed no obvious morphological differences among Brandisia chevalieri Bonati, B. discolor J.D.Hooker & Thomson, and B. scandens Bonati. This observation, coupled with previously established phylogenetic evidence, confirms B. chevalieri and B. scandens as synonyms of B. discolor. The issue concerning the type designation of B. discolor has been sorted out and clarified. A key to the species of Brandisia is also provided.